2014
DOI: 10.3109/21678421.2014.887118
|View full text |Cite
|
Sign up to set email alerts
|

Are we really closer to improving the diagnostic sensitivity in ALS patients with Awaji criteria?

Abstract: The Awaji criteria, recently introduced to increase diagnosis sensitivity in amyotrophic lateral sclerosis (ALS), equate the diagnostic significance of neurogenic electrophysiological changes to clinical signs of lower motor neuron dysfunction. They also increase the electrophysiological significance of fasciculation potentials (FPs). The aim of our study was to analyse whether the new parameters improve diagnostic sensitivity in ALS patients primarily diagnosed with the El Escorial criteria. Medical and elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 20 publications
3
21
1
Order By: Relevance
“…Several studies have been performed to examine the superiority of the AwC over the rEEC . A prospective study of 200 cases found that the AwC upgraded ALS diagnostic categories by 1 step in 25.7% of cases .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have been performed to examine the superiority of the AwC over the rEEC . A prospective study of 200 cases found that the AwC upgraded ALS diagnostic categories by 1 step in 25.7% of cases .…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Several studies have been performed to examine the superiority of the AwC over the rEEC. 7,[24][25][26][27] A prospective study of 200 cases found that the AwC upgraded ALS diagnostic categories by 1 step in 25.7% of cases. 25 Gawel and colleagues observed that, although the inclusion of fasciculation potentials as a sign of active denervation markedly increased the number of involved muscles, it did little to improve overall sensitivity for identification of an EDX-positive segment.…”
Section: Alsmentioning
confidence: 99%
See 1 more Smart Citation
“…They included 2 recent, less positive studies and did not include the strongly positive study of Okita et al The study by Higashihara et al was not included in our meta‐analysis, because it was not published at the time our manuscript was accepted. There are other important issues in the various papers analyzed that they may have overlooked.…”
mentioning
confidence: 99%
“…Moreover, looking at the Jang and Bae Table 2, it is apparent that other studies in which cranial‐innervated muscles were investigated “…when indicated…” or “…in very few patients…” were included. It is relevant that in another study they included, only 3 muscles were investigated in some patients, but from 4 different regions (Table 2). These differences in methodology are important and do not comply with the recommendations of the original description of the Awaji algorithm for electrophysiological assessment for diagnosis of ALS …”
mentioning
confidence: 99%